FRAX® Fracture Risks Are Associated with Coronary Artery Calcification Score - Chuang, Tzyy-Ling; Li, Yi-Da; Hsiao, Fu-Tsung; Chuang, Mei-Hua; Wang, Yuh-Feng (Disease Markers, 2017)
Purpose. To examine the association between fracture risk assessment tool (FRAX) scores and coronary artery calcification (CAC) score in adults. Methods. The medical records of 81 adults who underwent both coronary computed tomography and bone mineral density (BMD) studies in a package during their health exams were reviewed at a regional hospital in Southern Taiwan. Data collected included health history, anthropomorphic characteristics, clinical laboratory results, and BMD. Fracture risk was determined using FRAX. Univariate and multivariate linear regression analysis were used to assess the association between CAC score and 10-year probability of hip fracture (HF) and major osteoporotic fracture (MOF) determined by FRAX. Results. The mean age of the patients was 55.8 years, and 63.0% were male. Univariate linear regression analysis showed that increases in MOF and HF risks, as measured by FRAX, were significantly and positively associated with CAC score. Multiple linear regression analysis adjusting for potential confounders showed that CAC score remained significantly associated with four FRAX indicators, including right MOF (r=0.45, P<0.001), left MOF (r=0.31, P=0.021), right HF (r=0.38, P=0.001), and left HF (r=0.23, P=0.049). Conclusions. Increased risks of MOF and HF as determined by FRAX were significantly and independently associated with CAC score.